Presentation by Dr. Luis Bernardo Díaz of the Conference on Psychoanalysis and Law by Dr. Leonardo Ortega - Ortega, Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The links between law and psychology are not as recent as one might think. The subject of the psychological study of the offender or the suicide was always the order of the day. The discipline of legal psychology has been raised on many occasions, from a positivist and instrumental perspective, such as the management of juries, prison treatment, the resocialization of the offender or social deviation. Following the dictatorships and horrors of the twentieth century, such as concentration camps or the Armenian genocide, psychoanalysis enters into important contributions.